The introduction of the distributed ledger technology in banking system as an alernative for Single European Payment Area solutions - Michal Elzbieta Janton-Drozdowska; Alicja Mikolajewicz-Wozniak (Institute of Economic Research (IER), 2017)
The year 2016 ended the period of migration from national payment services to the SEPA instruments and it has become apparent that some problems remained unresolved. Overcoming them requires finding suitable technological solutions. The potential of distributed ledger technology (DLT) is currently explored by financial sector and its implementation may affect the SEPA schemes in a variety of dimensions. The aim of the article is to determine the potential impact of the DLT transfer to banking sector on the future SEPA's functioning. The paper presents SEPA's assumptions and the project's current status as well as DLT's concept. It describes the technology transfer implications for banking industry and compares currently operating SEPA schemes with those based on DLT. It also indicates opportunities and threats being the consequence of the new technology implementation and their significance for SEPA.In the article the qualitative analysis is supplemented by the quantitative one. While characterizing the functioning of the main pillars of the SEPA Schemes the elements of descriptive statistics are used. The final conclusions are based on the comparative analysis of SEPA schemes and developed DLT applications. The existing problems might be solved by supplementing currently operating SEPA payment schemes with the applications based on DLT. The developed systems shall provide required real-time processing and a global reach as well as extend the SEPA schemes' functionalities with the ability to transfer other currencies. The technology implementation shall result not only in new financial products but first of all - in creating new business models. Consequently, we shall expect the modification of currently operating SEPA schemes, based rather on their supplement than total replacement in a short time horizon.
Keywords: F36; G15; G21; 330; SEPA; blockchain; distributed ledger technology; virtual currencies; financial integration